HUBUNGAN KUANTITAS DAN KUALITAS TIDUR DENGAN MEMORI KERJA SELAMA PANDEMI COVID-19 PADA MAHASISWA PRE-KLINIK FAKULTAS KEDOKTERAN UNIVERSITAS NASIONAL VETERAN JAKARTA - Nirmala Radia Hasanah (2022)
Medical students are at risk for deprivation of sleep quantity and poor sleep quality, especially during the COVID-19 pandemic. Poor sleep quantity and quality can affect working memory. Working memory plays an important role in processing information such as language comprehension, reasoning, and learning. This study aims to determine the relationship between sleep quantity and quality with working memory during the COVID-19 pandemic in pre-clinical medical students. This study used cross-sectional. Total random sampling technique was used for a sample of 64 people. The instruments used are the Pittsburgh Sleep Quality Index and the Working Memory Questionnaire. This study was conducted on 64 samples of 7th semester medical students with the median score of respondent's sleep duration was 5 (3-8), PSQI score 10 (2-17), and WMQ score 27.5 (2-75). The results of the Spearman correlation test showed a relationship between sleep quantity and working memory (p = 0.000; r = -0.482), and the relationship between sleep quality and working memory (p = 0.000; r = 0.456). It can be concluded that there is a significant relationship between the quantity and quality of sleep with working memory